Correction of Maxillary canine- Lateral Incisor Transposisition by fexed Appliance (case report) - Dr.drg. Tita Ratya Utari, Sp.Ort (Prosiding Forum komunikasi ilmiah, 2012)
Transposition has been described as an interchange in the position of two permanent teeeth within the same quadrant of the dental arch. the maxillary permanent caninels the tooth most frequently involved in transposition, most often with the first premolar and less often with the lateral incisor, rarely with the central incisor and extremely rarely with the second premolar or first molar